An assessment of the biotechnological use of hemoglobin modulation in cereals. Issue 4 (28th October 2013) - Hebelstrup, Kim H.; Shah, Jay K.; Simpson, Catherine; Schjoerring, Jan K.; Mandon, Julien; Cristescu, Simona M.; Harren, Frans J. M.; Christiansen, Michael W.; Mur, Luis A. J.; Igamberdiev, Abir U.
<x xml:space="preserve">Abstract</x> Non‐symbiotic hemoglobin (nsHb) genes are ubiquitous in plants, but their biological functions have mostly been studied in model plant species rather than in crops. nsHb influences cell signaling and metabolism by modulating the levels of nitric oxide (NO). Class 1 nsHb is upregulated under hypoxia and is involved in various biotic and abiotic stress responses. Ectopic overexpression of nsHb in Arabidopsis thaliana accelerates development, whilst targeted overexpression in seeds can increase seed yield. Such observations suggest that manipulating nsHb could be a valid biotechnological target. We studied the effects of overexpression of class 1 nsHb in the monocotyledonous crop plant barley (Hordeum vulgare cv. Golden Promise). nsHb was shown to be involved in NO metabolism in barley, as ectopic overexpression reduced the amount of NO released during hypoxia. Further, as in Arabidopsis, nsHb overexpression compromised basal resistance toward pathogens in barley. However, unlike Arabidopsis, nsHb ectopic overexpression delayed growth and development in barley, and seed specific overexpression reduced seed yield. Thus, nsHb overexpression in barley does not seem to be an efficient strategy for increasing yield in cereal crops. These findings highlight the necessity for using actual crop plants rather than laboratory model plants when assessing the effects of biotechnological approaches to crop improvement.